Linear vs. Visual Cognitive Style and Faceted vs. Visual Interaction in Digital Library User Interfaces - Shiri, Ali; Ruecker, Stan; Murphy, Emily (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The paper examines the relationships between users’ cognitive and learning styles, their preferences for visual or faceted search user interfaces, and their information seeking strategies, in the context of a user-centred evaluation of two user interfaces for digital libraries, namely Searchling and T-Saurus (Shiri et al. 2011). Both interfaces provide access to multilingual libraries through interfaces that leverage the controlled vocabularies contained in multilingual thesauri. Cette communication examine les liens entre les styles cognitifs et d’apprentissage des utilisateurs, leurs préférences pour des interfaces de recherche visuelle ou par facette ainsi que leurs stratégies de recherche d’information, dans le contexte d’une évaluation centrée sur l’utilisateur de deux interfaces de bibliothèques numériques, soit Searchling et T-Saurus (Shiri et al., 2011). Les deux interfaces donnent accès à des bibliothèques multilingues en misant sur le vocabulaire contrôlé de thésaurus multilingues.